STUDENTS’ PERCEPTION OF THE IMPLEMENTATION OF THE INTEGRATING OF FOUR SKILLS IN TEACHING PRONUNCIATION - Amalia Ila (ELITE JOURNAL, 2019)
Pronunciation is one important aspect which determines the intelligibility of spoken language. The aim of this study was to identify the students’ perception of the integrating of four skills in teaching pronunciation, especially in teaching past tense verbs. The participants of the study included 30 students of English education department, Faculty of Education and Teacher Training of UIN “SMH” Banten. Collecting the data, the researcher used Likert-scale questionnaires. The questionnaire covered some aspects of basic principles of integrated lesson proposed by Oxford (2001). The data then analyzed using the descriptive statistical analysis to find out the percentage of each item of the questionnaire. The result showed that the majority of the students were comfortable with the integration of four skills in teaching pronunciation and enjoyed the activities and tasks in the classroom. The study also revealed that learning pronunciation integrated with other skills such as reading, writing, listening, speaking, was very useful to enhance the students’ communicative competence. Repetition combined with the use of audio-based resources as well as authentic materials were still considered very helpful for the students to practice pronunciation.